Editorial: Advances of the anthropological theory of the didactic - Chaachoua, Hamid; Bessot, Annie; Almouloud, Saddo Ag (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Advances of the anthropological theory of the didactic